1990
DOI: 10.1002/etc.5620090512
|View full text |Cite
|
Sign up to set email alerts
|

Ecological fate, effects and prospects for the elimination of environmental polychlorinated biphenyls (PCBs)

Abstract: Polychloiinated biphenyls (PCBs) present an environmental health hazard of global scale and man-made origin. Their impact on nearly every member of the biota results in a wide range of interacting negative effects. Due to their chemical nature, these recalcitrant toxicants are poised to enter and bioaccumulate in the food web. Recent advances in biodegradation research and molecular biology have shown that natural microorganisms and genetically modified bacterial strains could be used to decontaminate PCB-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(14 citation statements)
references
References 106 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…It is estimated that 70% of the world's production of PCBs are still in use or in stock and therefore it is likely that PCB contamination will continue to pose an environmental threat (Sumpter et al 1997). Indeed, it is recognized that PCBs will remain in the environment over geological time (Hooper et al 1990). PCBs are globally distributed, and are found predominantly in sediments in the aquatic environment.…”
mentioning
confidence: 99%
“…It is estimated that 70% of the world's production of PCBs are still in use or in stock and therefore it is likely that PCB contamination will continue to pose an environmental threat (Sumpter et al 1997). Indeed, it is recognized that PCBs will remain in the environment over geological time (Hooper et al 1990). PCBs are globally distributed, and are found predominantly in sediments in the aquatic environment.…”
mentioning
confidence: 99%
“…CBs and related chlorinated aromatic compounds, such as 1,1,1-trichloro-2,2-bis(p-chlorophenyl)ethane (DDT) and 2,4,7,8-tetrachlorodibenzodioxin, are also suspected of interfering with reproduction and development of wildlife chronically exposed to contaminated water, sediment, and food (23,32,35). The high cost and public opposition to current physical remediation technologies have stimulated interest in the use of microorganisms for bioremediation of CB-contaminated sites (25,43,46). Since the demonstration that two strains of Achromobacter could degrade mono-and dichlorobiphenyls by Ahmed and Focht (1), numerous studies have shown that a broad diversity of bacteria have the ability to degrade many of the different CB congeners that contaminate the environment (3,16,24,39).…”
mentioning
confidence: 99%
“…Since the demonstration that two strains of Achromobacter could degrade mono-and dichlorobiphenyls by Ahmed and Focht (1), numerous studies have shown that a broad diversity of bacteria have the ability to degrade many of the different CB congeners that contaminate the environment (3,16,24,39). While natural microbial degradation of CBs is constrained by a combination of physical, chemical, and biological factors (25), development of effective bioremediation strategies will be aided by an understanding of the biochemical mechanisms involved in the mineralization of CBs.…”
mentioning
confidence: 99%
“…Their presence is a cause for great concern because they are suspected of having adverse effects on human and animal health. The high cost and public opposition to current physical and chemical remediation technologies have stimulated interest in the use of microorganisms for bioremediation of PCB-contaminated sites (Hooper et al 1990;Shannon et al 1994;Unterman et al 1998). Quite unfortunately, no effective bioremediation strategies have yet been developed for the restoration of sites contaminated with PCBs, but the progress made in recent years has been sufficiently encouraging to lead investigators to believe that bacterial strains with enhanced capacity to degrade these pollutants can be developed.…”
Section: Introductionmentioning
confidence: 98%